Retaining venous access and eliminating radiation exposure during Hickman-Broviac catheter replacement for difficult-line insertion patients with intestinal failure - Justin T Chu; Chee-Chee Koh; Yun Chen (Formosan Journal of Surgery, 2021)
Hickman-Broviac catheters are commonly used to access central veins for the purposes of intravenous nutrition delivery for intestinal failure (IF) patients. While these catheters are good options for accessing central veins, they often have to be replaced if catheter-related infection or occlusion occurs. Frequent replacement can be hampered by the limited venous access sites in these patients and reduce the access site's lifespan. In this technical note, we describe a technique to periodically replace Hickman-Broviac catheters without having to create a new venous access site. Without requiring radiation exposure by standardized guidewire insertion, we safely utilize the fibrotic pseudocapsule that forms around the old catheter to guide the new catheter to the central veins while creating a different exit site to prevent infection. The procedure should be performed periodically – we advocate annually – before catheter-related infection occurs. In this way, we hope to be able to provide a solution for IF patients who require life-long catheter usage but have limited venous access, while also reducing the risk of related injuries such as pneumothorax, arterial injury, or radiation exposure.